2004
DOI: 10.1111/j.1365-2036.2004.02259.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: the eosinophil as a therapeutic target in gastrointestinal disease

Abstract: SUMMARYElevated levels of eosinophils in the gastrointestinal tract is a common feature of numerous gastrointestinal disorders including food allergy, parasitic infections, gastro-oesophageal reflux, eosinophilic oesophagitis, eosinophilic gastroenteritis, allergic colitis and inflammatory bowel diseases. Recently, clinical and experimental studies have provided evidence that eosinophils have a critical role in the pathophysiology of eosinophilassociated gastrointestinal disease. Collectively, these studies ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 72 publications
(128 reference statements)
1
29
0
5
Order By: Relevance
“…One study suggested this therapeutic strategy. 104 First, they recommended specifi c allergy avoidance (airborne and dietary). If this failed to improve EGID pathology, then they recommended glucocorticoid therapy, fi rst starting with topical delivery and then considering systemic delivery.…”
Section: Treatmentmentioning
confidence: 99%
“…One study suggested this therapeutic strategy. 104 First, they recommended specifi c allergy avoidance (airborne and dietary). If this failed to improve EGID pathology, then they recommended glucocorticoid therapy, fi rst starting with topical delivery and then considering systemic delivery.…”
Section: Treatmentmentioning
confidence: 99%
“…Eosinophils are multifunctional proinflammatory peripheral blood leukocytes that have been implicated in a number of immune-mediated diseases of the gastrointestinal (GI) tract, particularly allergic disorders [1][2][3][4][5][6][7]. Activated degranulating eosinophils release major basic protein, which can decrease mucosal epithelial barrier function and contribute to the epithelial cell damage seen in inflammatory bowel diseases, suggesting a role for eosinophils in their pathogenensis [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism underlying the development of concurrent PSC and eosinophilic enteritis has not been elucidated to date. However, possible mechanisms include the involvement of factors that promote the proliferation of eosinophils in the bone marrow and their migration to inflammatory tissue, as well as the expression of eosinophilic granular proteins at affected sites, including eosinophil peroxidase (EPO) (14,15). These factors were not assessed in In the current case, eosinophilic cholangitis is another differential diagnosis of PSC.…”
Section: Discussionmentioning
confidence: 90%